Сон Макара: святочный рассказ / В. Г. Короленко - Короленко Владимир Галактионович (Удмуртия, 2003)
Экземпляры: ф.1 (2003) / Инвентарный номер: 47193 / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: К 68 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1-44